Sufism and the Urban Society's Economy: Study of the Economic Dimensions of the Tarekat Siddiqiyah In Indonesia - Siswoyo Aris Munandar (Al Qalam, 2022)
Tarekat is often regarded as the decline of Islam. With his teachings zuhud, poor, and tawakal are considered activities of the tarekat from worldly life so that the life they live is fatalistic and is like the world. Some of the interesting phenomena of the Tarekat Shiddiqiyah can be seen from the economic behavior of its adherents, especially in developing business units that can support the increasingly rapid development of the tarekat in Indonesia. Therefore, the author is very interested in researching the tarekat. To answer that, the writer formulates the problem: how is business development in the Tarekat Shiddiqiyah? In conducting the research, the author uses qualitative research methods with a phenomenological approach. The selection of organizations is based on the Tarekat Shiddiqiyah in Indonesia as the object of research on phenomena and information on groups with their characteristics or characteristics relevant to the problem to be studied, namely the business of the tarekat Shiddiqiyah. The results of this study indicate that this phenomenon can be reached because this tarekat has its uniqueness, especially from the aspect of its teachings and views on world life, which are different from other tarekat with his teachings, his work in education, society, politics, and economics.